Methods of wintering steer calves that are to be grazed a full season and sold off grass - Baker, F.H.; Cox, R.F.; Smith, E.F.; Good, D.L.; Walker, G.L. (Kansas Agricultural Experiment Station, 2012)
Forty choice Hereford steer calves, purchased from the Lonker Ranch in Barber county, Kansas, were used in this experiment. The steers of Lot 1 were wintered in a dry lot at the experimental barn, while those of the other lots were wintered on dry bluestem pasture at the experimental range unit. The pastures had been stocked at a normal rate the previous summer; adequate grass remained for winter pasture. The calves of Lots 2, 3, and 4 were moved from pasture to pasture monthly to minimize any differences due to pasture.
Keywords: Beef; Management; Protein; Dry bluestem pasture